Intellectual Capital Disclosure and the Effecting Factor on Official Website of Higher Education in Indonesia - Nika Esti Rahayu; Doddy Setiawan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to describe the level of intellectual capital disclosure and examine the effect of age, size, and internationality on the intellectual capital disclosure (ICD) of higher education in Indonesia. This study also sees the difference in intellectual capital disclosure between public and private higher education. This study uses 88 official websites of higher education in Indonesia. The ICD component used in this study is a framework comprising 60-item—testing tools for multiple linear regression analysis with a significance level of 0.05. The results obtained are: (1) size has a significant effect on intellectual capital disclosure; (2) age and internationality haven’t a significant effect on intellectual capital disclosure; and (3) intellectual capital disclosure of public higher education and private higher education has a different pattern. Public higher education is more likely to disclose information about human, structural, and relational capital in a narrative format. Meanwhile, private higher education is more likely to disclose structural and relational capital information in a narrative format but does not reveal information about human capital. This study contributes to the reference related to the pattern of intellectual capital disclosure among higher education (public and private higher education) and its affecting factors.